Investigation of bacteremia after orthodontic bonding - (:unkn) unknown (MOSBY-YEAR BOOK INC, 1999)
The aim of this study was to assess the incidence of bacteremia after orthodontic banding. The study was conducted on 40 healthy orthodontic patients with good oral hygiene. Venous blood samples were obtained with a strict aseptic technique before and after fitting of a molar band in each patient. Microbiologic evaluation of the samples revealed a postoperative bacteremia incidence of 7.5%.
Keywords: MANAGEMENT; CHILDREN